TANTANGAN DAN PELUANG PENDIDIKAN ISLAM DI ERA DIGITALISASI DALAM SUDUT PANDANG FILSAFAT PENDIDIKAN ISLAM - Hilda Wahyuni; Ahmad Barizi; Akhmad Nurul Kawakip; Wilda Al Aluf; Iqbal Ardiansyah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
The presence of the digital age has had a significant influence on the world of Islamic education today. The changes that occur, of course, cannot be left alone by Islamic education policymakers. Now, Islamic education is faced with significant challenges as well as promising opportunities in this era of digitalization. This is also inseparable from the role of philosophy in the realm of Islamic education, which is one of the determinants of Muslim education policy. This research aims to provide a new perspective on Islamic education regarding the presence of the era of digitalization in life. The results explain the need for innovation in Islamic education so that it is not eroded by the era of digitalization. Through the use of digital technology, Islamic education is expected to be at the forefront of developing methods, media, and curricula utilizing digital technology intelligence.